Effects of Life and Non-Life Insurance on Economic Growth in Nigeria: An Autoregressive Distributed Lag (ARDL) Approach (Global Journal of Management and Business Research, 2016)
This paper investigates separately the effects of life and non-life insurance on economic growth in Nigeria from 1976 to 2013. The Autoregressive Distributed lags (ARDL) was adopted given the different order of integration of the variables of interest. After estimating a growth model, the bound test shows a long run relationship to exist among economic life, non-life insurance and economic growth in Nigeria over the period of study. The long run and the short run dynamics further confirms the positive and significant contribution of life and non-life insurance on economic growth in Nigeria. The paper concludes that life and non-life insurance acts as complements to economic growth in Nigeria rather substitutes.
Keywords: life premium; non-life premium; economic growth; co-integration; ARDL; nigeria